Daily patterns of ethanol drinking in adolescent and adult, male and female, high alcohol drinking (HAD) replicate lines of rats - Dhaher, Ronnie (Pharmacol Biochem Behav, 2012)
The rationale for our study was to determine the pattern of ethanol drinking by the high alcohol-drinking (HAD) replicate lines of rats during adolescence and adulthood in both male and female rats. Rats were given 30 days of 24 h free-choice access to ethanol (15%, v/v) and water, with ad lib access to food, starting at the beginning of adolescence (PND 30) or adulthood (PND 90). Water and alcohol drinking patterns were monitored 22 h/day with a “lickometer” set-up. The results indicated that adolescent HAD-1 and HAD-2 males consumed the greatest levels of ethanol and had the most well defined ethanol licking binges among the age and sex groups with increasing levels of ethanol consumption throughout adolescence. In addition, following the first week of adolescence, male and female HAD-1 and HAD-2 rats differed in both ethanol consumption levels and ethanol licking behavior. Adult HAD-1 male and female rats did not differ from one another and their ethanol intake or licking behaviors did not change significantly over weeks. Adult HAD-2 male rats maintained a relatively constant level of ethanol consumption across weeks, whereas adult HAD-2 female rats increased ethanol consumption levels over weeks, peaking during the third week when they consumed more than their adult male counterparts. The results indicate that the HAD rat lines could be used as an effective animal model to examine the development of ethanol consumption and binge drinking in adolescent male and female rats providing information on the long-range consequences of adolescent alcohol drinking.